2014
DOI: 10.3989/redc.2014.4.1186
|View full text |Cite
|
Sign up to set email alerts
|

La colaboración científica: principales líneas de investigación y retos de futuro

Abstract: Resumen: La construcción del conocimiento es un proceso cooperativo que se ha intensificado considerablemente a lo largo de las últimas décadas, involucrando cualquier iniciativa de investigación a un número cada vez mayor de investigadores, instituciones, disciplinas y países. El presente estudio realiza una revisión bibliográfica de la literatura sobre colaboración científica. Se identifican los trabajos pioneros del área, el tipo de estudio y las variables analizadas. Se comenta la aproximación "clásica", b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 75 publications
(16 reference statements)
0
18
0
11
Order By: Relevance
“…Scientific collaboration plays an essential role in the professional activity of researchers (González-Alcaide and Gómez-Ferri, 2014). Although research by 'solo scientists' still predominates in some science areas such as humanities, individual activity is generally guided by membership or inclusion in research teams or research organisations, whether academic or a different type.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific collaboration plays an essential role in the professional activity of researchers (González-Alcaide and Gómez-Ferri, 2014). Although research by 'solo scientists' still predominates in some science areas such as humanities, individual activity is generally guided by membership or inclusion in research teams or research organisations, whether academic or a different type.…”
Section: Introductionmentioning
confidence: 99%
“…And the umbrella of the group or presumed collaboration might be used to hide mediocre and arriviste researchers, student promotion, or favour exchanges; collaboration might also be a merely utilitarian means to an end, e.g. access to funding, which has nothing to do with genuine, knowledge-boosting cooperation (González-Alcaide and Gómez-Ferri, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, it is difficult to measure individual contributions to research carried out in collaboration, and secondly, different studies have reported the inflationary tendencies of collaboration indexes (Cronin, 2001). Thus, a number of challenges need to be addressed before integrating scientific collaboration as a variable in research evaluation processes (Cronin and Weaver, 1995;González-Alcaide and Gómez-Ferri, 2014). These include further in-depth analysis into the processes that scientists use to attribute merit through publications in different disciplines and particularly the clarification of specific aspects such as author order, the role of the corresponding author, and other elements such as the acknowledgments.…”
Section: Discussion Individual Indicators For Scientific Activity Comentioning
confidence: 99%
“…In view of the increased output of scientific articles over the past decades, the literature review would be very difficult to undertake using traditional qualitative methods. It is therefore necessary to handle bibliometric techniques for complementing the literature review in order to trace the origins of the study and locate the scientific community's most relevant papers and contributions (González-Alcaide and Gómez Ferri, 2014).…”
Section: Introductionmentioning
confidence: 99%